Estudo de nós soldados tipo K de treliças planas constituídas por seções tubulares circulares de aço - Carolina Rodrigues Lemos Lameiras (2008)
The trusses of circular hollow sections, should be checked about last limit states of plastification and punching shear of chord wall. The standards AWS D1.1: 2002, ANSI /IACS 360-05 and EN 1993-1-8:2005 have virtually identical procedures for the verification of these limits states, based mainly in the works of Wardenier et al. (1991) and Packer and Henderson (1997). Moreover, the Brazilian standard ABNT NBR 8800: 2008 does not present any specific procedure, recommending the use of foreign standards, with necessary adjustments to maintain their security level. This paper seeks simulate numerically, throughthe program ABAQUS, based on the finite elements method, the behavior until the collapse, identifying the last limits states, of joint K. The numerical modeling considered the geometrical and material non-linearity and large displacements. In several cases, to assess itsinfluence on results was additionally simulated welding between branches and chord. Models were created with two different diameters for the branches, and for each diameter, two values for the thickness of the wall, as well as three different angles between branches and chord.The results, considering and disregarding the influence of weld, were critically analyzed and compared with those provided by the above standards.